Mitochondrial oxidative DNA damage and exposure to particulate air pollution in mother-newborn pairs - Grevendonk, Lotte; Janssen, Bram G.; Vanpoucke, Charlotte; Lefebvre, Wouter; Hoxha, Mirjam; Bollati, Valentina; Nawrot, Tim S. (Environmental health, 2016)
Background Studies emphasize the importance of particulate matter (PM) in the formation of reactive oxygen species and inflammation. We hypothesized that PM exposure during different time windows in pregnancy influences mitochondrial 8-hydroxy-2′-deoxyguanosine (8-OHdG) levels, which is an established biomarker for oxidative stress, in both maternal and foetal blood. Methods We investigated maternal ( n = 224) and cord blood ( n = 293) from mother-newborn pairs that were enrolled in the ENVIR ON AGE birth cohort. We determined mitochondrial 8-OHdG by quantitative polymerase chain reaction (qPCR). Multivariable regression models were used to assess the association between mitochondrial 8-OHdG with PM 10 and PM 2.5 exposure over various time windows during pregnancy . Results In multivariable analysis, PM 10 exposure during the entire pregnancy was positively associated with levels of mitochondrial 8-OHdG in maternal blood. For an IQR increment in PM 10 exposure an increase of 18.3 % (95 % confidence interval (CI): 5.6 to 33.4 %, p = 0.004) in 8-OHdG was observed. PM 10 exposure during the last trimester of pregnancy was positively associated with levels of 8-OHdG (28.1, 95 % CI: 8.6 to 51.2 %, p = 0.004, for an IQR increment in PM 10 ). In a similar way, PM 2.5 exposure was significantly associated with an increase of mitochondrial 8-OHdG levels in maternal blood during the entire pregnancy (13.9, 95 % CI: 0.4 to 29.4 %, p = 0.04 for an IQR increment in PM 2.5 exposure) and third trimester of pregnancy (28.1, 95 % CI: 3.6 to 58.4 %, p = 0.02 for an IQR increment in PM 2.5 exposure). In umbilical cord blood, 8-OHdG levels were significantly associated with PM 10 exposure during first and second trimester of pregnancy with respectively an increase of 23.0 % (95 % CI: 5.9 to 42.8 %, p = 0.007) and 16.6 % (95 % CI: 1.8 to 33.5 %, p = 0.03) for an IQR increment in PM 10 exposure. Conclusions We found PM-associated increased mitochondrial oxidative DNA damage during pregnancy in both mothers and their newborns. Accordingly, our study showed that particulate air pollution exposure in early life plays a role in increasing systemic oxidative stress, at the level of the mitochondria, both in mother and foetus.